2020
DOI: 10.1200/go.20.00041
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Pediatric Cancer in Four Eastern Mediterranean Countries: A Comparative Assessment

Abstract: PURPOSE Cancer is a leading cause of death among children in the Eastern Mediterranean region, where conflict and economic downturn place additional burden on the health sector. In this context, using economic evidence to inform policy decisions is crucial for maximizing health outcomes from available resources. We summarized the available evidence on the economics of pediatric cancer in Jordan, Lebanon, the occupied Palestinian territory, and Turkey. METHODS A scoping review was performed of seven academic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“… 30 , 31 There is a lack of data about cost-effectiveness of paediatric cancer treatment in the Eastern Mediterranean countries. 32 …”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 There is a lack of data about cost-effectiveness of paediatric cancer treatment in the Eastern Mediterranean countries. 32 …”
Section: Discussionmentioning
confidence: 99%
“…In African countries without subsidized cancer care or UHC, and those where UHC does not include adequate cancer care, parents, and caregivers are often unable to pay medical costs 11 . Payment for expensive care can further impoverish families already in precarious financial circumstances in their quest to save the lives of their children as shown in India 27 and Lebanon 28 …”
Section: Discussionmentioning
confidence: 99%
“…Areas of research that deserve special consideration include cost-effectiveness of pediatric cancer care and outcome studies [4]. Cutting-edge research is available in multiple centers in the Arab world, and many centers are already involved in collaborative international trials.…”
Section: Research/collaborationmentioning
confidence: 99%
“…It is noted that major gaps in our knowledge regarding the true burden of pediatric cancer in the Arab world exists. In a scoping review by Gheorghe et al, where all literature from three Arab countries and Turkey were reviewed, it was revealed that much needs to be done to appreciate the impact of this problem [4]. One particular area of concern was the lack of reliable data regarding the outcome of pediatric cancer on national levels.…”
Section: Introductionmentioning
confidence: 99%